SPREAD OF LOW PATHOGENIC AVIAN INFLUENZA А/Н9N2 IN THE WORLD AND RUSSIAN FEDERATION. CHALLENGES OF DISEASE ERADICATION - M. S. Volkov; A. V. Varkentin; V. N. Irza (Ветеринария сегодня)
The paper demonstrates data on global and national spread of subtype H9 low pathogenic avian influenza in poultry. Due to no need of the mandatory disease notification to the OIE, published data are used for the analysis of the infection spread. Cases of combined low pathogenic avian influenza clinical manifestation in poultry population are described. Challenges of the infection eradication are addressed. Global spread of А/Н9 virus in poultry, its rapid evolution and zoonotic potential require close attention. Since the disease signs and clinical course are similar to the ones of other avian infectious diseases (Newcastle disease, infectious laryngotracheitis, infectious bronchitis, metapneumovirus infection, mycoplasmosis, infectious coryza, etc.), the routine laboratory diagnosis should include tests for low pathogenic avian influenza thus facilitating the rapid response to the threat. Н9 virus circulation is reflected not only in the physical condition of birds and their productivity, but it also affects the live vaccines’ efficacy during scheduled immunizations through the reduction of their protective effect and increase of post-vaccination reactions. In spite of the availability of specific prevention, the opinions of the researchers divided between its opponents and proponents. On the one hand, the vaccination eliminates the economic loses and the virus escape into the environment, but on the other hand, it can aid to “silent” spread of the virus and its established variation that is typical in case of low strength of the poultry population immunity.